Analysis of factors affecting company value with moderation of profitability - Sri Wahyuni (Jurnal Mantik, 2024)
This research aims to examine the influence of transfer pricing, tax planning and tax avoidance on company value, with profitability as a moderating variable. The population in this research is mining companies listed on the Indonesia Stock Exchange in 2020 - 2022. The sampling technique used was purposive sampling and resulted in a sample of 41 companies and 104 observation samples. The model used is Moderate Regression Analysis (MRA). The results of this research show that transfer pricing, tax planning and tax avoidance have no effect on company value, and profitability as a moderating variable cannot moderate the influence of transfer pricing, tax planning and tax avoidance on company value.